Characterization of Infections With Extended-Spectrum β-Lactamase Producing Escherichia coli and Klebsiella Species at a Major Military Medical Center. Issue 7 (1st July 2014) - Koren, Michael; Demons, Samandra; Murray, Clinton; Mahlen, Steven; Schofield, Christina
ABSTRACT: This study represents a review of the incidence of extended-spectrum β-lactamase (ESBL) producing Escherichia coli and Klebsiella species causing infections over a 7-year period and provides a comparison of patient demographics, comorbidities, and ESBL subtypes between community-associated (CA) versus health care–associated (HA) infections. All ESBL-producing bacterial isolates between 2003 and May 2011 at Madigan Army Medical Center were evaluated and reviewed. Polymerase chain reaction (PCR) for ESBL subtypes TEM, SHV, and CTX-M was performed. Demographics and comorbidities associated with infection, ESBL subtype, and antibiotic susceptibility were compared for HA and CA infection. A total of 122 isolates were included in the analysis. From 2005 to 2010, incidence of ESBLs in E coli increased from 0.13% to 1.0%, and incidence in Klebsiella species rose from 1.0% to 2.55%. CA infections were more likely in females ( p < 0.01), age <60 ( p < 0.01), urinary source ( p < 0.01), and recurrent urinary tract infections ( p = 0.02). 42% of CA infections had no associated comorbidity. CTX-M was the predominant subtype in CA infections. Coresistance was high in both HA and CA infection. These data emphasize the need for ongoing monitoring of local microbial epidemiologic trends as changes in prescribing practices may become necessary if resistance continues to spread.